Preparation method of nano composite film
By forming a thermal conductive layer on the nanofiber membrane, the problem of poor thermal conductivity of the existing radiation refrigeration film materials is solved, and the efficient radiation refrigeration and thermal conductivity of the nanocomposite film is achieved, thereby reducing production costs and weight.
Patent Information
- Application Number
- CN202411640870.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
AI Technical Summary
The existing radiation refrigeration film has poor thermal conductivity, which limits its application in certain special environments. At the same time, the existing thermal conductivity coating is inconvenient to operate, expensive equipment, and increases the weight and cost of nano-film materials.
The polymer powder is dissolved in N,N-dimethylformamide to form a polymer solution, and nanoparticles with selective emission characteristics are added to form a nanocomposite solution, and a nanofiber film is prepared, and then the thermally conductive mixture solution is scraped on its surface to form a thermally conductive layer to obtain a nanocomposite film.
The nanocomposite film has good radiation refrigeration and thermal conductivity. The temperature drop of radiation refrigeration is above 1°C and the thermal conductivity is above 0.5W/m*K, while reducing production costs and weight.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nanomaterials, and in particular to a method for preparing a nanocomposite film. Background Art
[0002] In the field of radiation cooling, the use of nanomaterials to prepare film materials with radiation cooling effects is an emerging technical means. Radiative cooling technology uses the characteristic of the "atmospheric window" to radiate heat directly into outer space, thereby achieving a cooling effect, and then adding some materials with strong mid-infrared emissivity to make the cooling effect better. This technology has the advantages of energy saving, environmental protection, and pollution-free, so it has broad application prospects in the fields of construction, aerospace, etc. However, existing radiation cooling film materials generally have the problem of poor thermal conductivity, which limits their application in certain special environments.
[0003] In the prior art, in order to improve the thermal conductivity of the nanofiber membrane, a coating with excellent thermal conductivity is usually applied to the nanofiber membrane. This coating can be a metal coating, a ceramic coating or a carbon-based coating. For example, a graphene coating can be deposited on the nanofiber membrane by a chemical vapor deposition (CVD) method to improve the thermal conductivity of the nanofiber membrane. In addition, a boron nitride coating can be applied to the nanofiber membrane by a sol-gel method to improve the thermal conductivity of the nanofiber membrane, but these methods are currently inconvenient to operate and the equipment is expensive.
[0004] However, there are some common problems in the existing technology when preparing nano-film materials with radiative cooling effects. First, while most radiative cooling materials achieve efficient heat dissipation, their thermal conductivity is insufficient, which greatly reduces the life of electronic and electrical equipment during use. Secondly, the existing thermal conductive coatings are usually thicker, which will increase the weight of the nano-film materials and reduce their mechanical properties. In addition, the existing thermal conductive coatings are usually expensive, which limits the commercial application of nano-film materials. Therefore, how to prepare nano-film materials with excellent thermal conductivity and good radiative cooling effects is a problem that needs to be solved urgently in this field.
[0005] The present invention solves at least one of the above problems. Summary of the invention
[0006] The purpose of the present application is to provide a method for preparing a nanocomposite film, wherein the nanocomposite film has both good radiation cooling performance and thermal conductivity.
[0007] The purpose of this application is achieved by the following technical solution: A method for preparing a nanocomposite film, comprising:
[0008] dissolving polymer powder in N,N-dimethylformamide to form a polymer solution;
[0009] Adding nanoparticles to the polymer solution to form a nanocomposite solution, wherein the nanoparticles have selective emission characteristics;
[0010] preparing a nanofiber membrane using the nanocomposite solution;
[0011] A thermally conductive mixed liquid is prepared by using thermally conductive powder, silicone oil, hydrogen-containing silicone oil, inhibitor, catalyst and dispersant;
[0012] The heat-conducting mixed liquid is scraped on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane to obtain a nanocomposite membrane.
[0013] The beneficial effect of the present application is that a nanocomposite solution is first formed by nanoparticles with selective emission characteristics and a polymer solution, and then a nanofiber membrane is prepared. Finally, a thermal conductive layer is scraped on the nanofiber membrane to obtain a nanocomposite membrane, so that the nanocomposite membrane of the present application has good radiation cooling performance and thermal conductivity. The temperature drop of the nanocomposite membrane for radiation cooling is above 1°C, and the thermal conductivity is above 0.5W / m*K.
[0014] In some possible implementations, the heat-conducting layer includes a first heat-conducting layer and a second heat-conducting layer stacked in sequence; and applying the heat-conducting mixed liquid on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane includes:
[0015] Evenly scraping a portion of the heat-conducting mixed liquid on the surface of the nanofiber membrane, and forming a first heat-conducting layer on the surface of the nanofiber membrane after drying;
[0016] The nanofiber membrane with the first heat-conducting layer formed on the surface is rotated 90 degrees, another part of the heat-conducting mixed liquid is evenly scraped on the surface of the first heat-conducting layer, and a second heat-conducting layer is formed on the surface of the first heat-conducting layer after drying.
[0017] In some possible implementations, in the nanocomposite solution, the mass fraction of the polymer solution is 8 wt % to 14 wt %; and the mass fraction of the nanoparticles is 0.1 wt % to 0.5 wt %.
[0018] In some possible implementations, by weight, the thermally conductive powder is 100 parts; the silicone oil is 1 to 10 parts; the hydrogen-containing silicone oil is 0.05 to 0.2 parts; the inhibitor is 0.01 to 0.1 parts; the catalyst is 0.01 to 0.1 parts; and the dispersant is 10 to 40 parts.
[0019] In some possible embodiments, preparing a nanofiber membrane from the nanocomposite solution by an electrospinning machine comprises:
[0020] The nanocomposite solution is placed in a syringe of an electrospinning machine to prepare a nanofiber membrane using an electrospinning process;
[0021] The flow rate of the nanocomposite solution is 0.3-1.2 ml / h; the voltage of the electrostatic spinning is 10-30 KV; the temperature of the electrostatic spinning is 30±3; and the relative humidity of the electrostatic spinning is 40%±5%.
[0022] In some possible implementations, the polymer includes one or more of PVDF, PVC, PI, PU, and TPX; and / or the molecular weight of the polymer is 500,000-1,000,000.
[0023] In some possible implementations, the nanoparticles include one or more of SiO2, ZnO, Al2O3, TiO2, and ZnS; and / or the average particle size of the nanoparticles is 0.2 to 12 um.
[0024] In some possible implementations, the thermally conductive powder includes one or more of Al2O3, AlN, BN, Si3N4, Al(OH)3, Ag, and diamond; and / or the average particle size of the thermally conductive powder is 0.4 to 20 um.
[0025] In some possible implementations, the silicone oil includes one or more of vinyl silicone, methylphenyl silicone, polydimethyl silicone, and hydroxy silicone.
[0026] In some possible implementations, the hydrogen-containing silicone oil includes one or more of terminal hydrogen-containing silicone oil and side hydrogen-containing silicone oil.
[0027] In some possible implementations, the inhibitor includes one or more of acetylene alcohols, alkynyl siloxanes, and nitrates.
[0028] In some possible implementations, the catalyst includes one or more of an organic tin catalyst, an organic chromium catalyst, a platinum catalyst, and an organic titanium catalyst.
[0029] In some possible embodiments, the selected dispersant includes one or more of ethylene glycol, xylene, butyl ester, and dimethyl carbonate. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a schematic flow chart of a method for preparing a nanocomposite film according to an embodiment of the present application;
[0031] Figure 2 It is a flow chart of the preparation method of forming a thermal conductive layer on the nanofiber membrane in an embodiment of the present application. DETAILED DESCRIPTION
[0032] The example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; on the contrary, these embodiments are provided to make this application more comprehensive and complete and to fully convey the concept of the example embodiments to those skilled in the art.
[0033] See attached Figure 1 As shown, the embodiment of the present application provides a method for preparing a nanocomposite film, including steps S1 to S6.
[0034] Step S1: dissolving polymer powder in N,N-dimethylformamide to form a polymer solution.
[0035] The polymer in the present application may be one or more of PVDF (polyvinylidene fluoride), PVC (polyvinyl chloride), PI (polyimide), PU (polyurethane), and TPX (poly-4-methylpentene-1).
[0036] If the molecular weight of the polymer is too small, it is difficult to form a film, and if the molecular weight is too large, the performance of the film is poor. The molecular weight of the polymer can be 500,000 to 1,000,000. In a preferred embodiment, the molecular weight of the polymer is 500,000 to 700,000. By using polymers with the above molecular weight, the cooling performance of the nanocomposite film is better.
[0037] Step S2: adding nanoparticles into the polymer solution to form a nanocomposite solution, wherein the nanoparticles have selective emission characteristics.
[0038] The nanoparticles in the present application may be one or more of SiO2, ZnO, Al2O3, TiO2, and ZnS. The above nanoparticles have selective emission characteristics. By using the above nanoparticles, the nanocomposite film has good cooling performance.
[0039] Further, in the nanocomposite solution, the mass fraction of the nanoparticles is 0.1wt% to 0.5wt% by mass, and in some preferred embodiments, the mass fraction of the nanoparticles is 0.3wt%. With the nanoparticles at this mass fraction, the cooling performance of the nanocomposite film is better. The mass fraction of the polymer solution is 8wt% to 14wt%. In some preferred embodiments, the mass fraction of the polymer solution is 12wt%. With the polymer solution at this mass fraction, the cooling performance of the nanocomposite film is better.
[0040] In a preferred embodiment, the nanoparticles are SiO2, because of its high infrared emissivity, and the nanocomposite film has better cooling performance when SiO2 is used.
[0041] Furthermore, the average particle size of the nanoparticles is 0.2-12 um. In a preferred embodiment, the average particle size of the nanoparticles is 0.8-10 um. By using nanoparticles of the above particle size, the radiation cooling performance of the nanocomposite film is better.
[0042] Step S3: preparing a nanofiber membrane using the nanocomposite solution. In some embodiments, the nanocomposite solution is prepared into a nanofiber membrane using an electrospinning machine.
[0043] Specifically, the nanocomposite solution is placed in a syringe of an electrospinning machine, and the nanofiber membrane is prepared by an electrospinning process.
[0044] Exemplarily, the flow rate of the nanocomposite solution is adjusted to 0.3-1.2 ml / h by the microinjection pump of the electrospinning machine; the voltage of the electrospinning is 10-30 KV; the temperature of the electrospinning is 30±3; and the relative humidity of the electrospinning is 40%±5%.
[0045] In some preferred embodiments, the flow rate of the nanocomposite solution is 0.7 ml / h and the voltage of the electrospinning is 20 KV. Under these conditions, the surface properties of the nanocomposite film are better.
[0046] Step S4: preparing a heat-conducting mixed liquid by using heat-conducting powder, silicone oil, hydrogen-containing silicone oil, inhibitor, catalyst and dispersant.
[0047] In some embodiments, by weight, the thermally conductive powder is 100 parts; silicone oil is 1-10 parts; hydrogen-containing silicone oil is 0.05-0.2 parts; inhibitor is 0.01-0.1 parts; catalyst is 0.01-0.1 parts; and dispersant is 10-40 g. The nanocomposite film with this ratio has good thermal conductivity.
[0048] In some embodiments, the thermally conductive powder may be one or more of aluminum oxide (Al2O3), aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), aluminum hydroxide (Al(OH)3), silver (Ag), and diamond.
[0049] Furthermore, the average particle size of the thermally conductive powder is 0.4 to 20 um. In some preferred embodiments, the thermally conductive powder includes Al2O3 with an average particle size of 0.8 um, Al2O3 with an average particle size of 5 um, and Al2O3 with an average particle size of 10 um. The weight ratio thereof can be 1:1:1 or 1:1:2 or 1:1.5:3 or 1:2:3. The nanocomposite film under this specification has good thermal conductivity and radiation cooling performance.
[0050] In some embodiments, the silicone oil may be one or more of vinyl silicone, methylphenyl silicone, polydimethyl silicone, and hydroxy silicone.
[0051] The hydrogen-containing silicone oil may be one or more of terminal hydrogen-containing silicone oil and side hydrogen-containing silicone oil. The inhibitor may be one or more of acetylene alcohols, alkynyl siloxanes, and nitrates. Among them, acetylene alcohols may be 1-ethynyl cyclohexanol, methyl butynol, etc.; nitrates may be nitroglycerin, sodium nitrite, etc.
[0052] The catalyst may be one or more of an organic tin catalyst, an organic chromium catalyst, a platinum catalyst, and an organic titanium catalyst.
[0053] The dispersant includes one or more of ethylene glycol, xylene, butyl ester, and dimethyl carbonate (DMC).
[0054] Step S5: scraping the heat-conducting mixed liquid on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane to obtain a nanocomposite membrane.
[0055] In a specific embodiment, the heat-conducting layer includes a first heat-conducting layer and a second heat-conducting layer which are stacked in sequence; Figure 2 As shown, applying the heat-conducting mixed liquid on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane includes steps S51-S52.
[0056] Step S51: evenly scrape a portion of the heat-conducting mixed liquid onto the surface of the nanofiber membrane, and form a first heat-conducting layer on the surface of the nanofiber membrane after drying.
[0057] Step S52: rotate the nanofiber membrane with the first heat-conducting layer on the surface by 90 degrees, and evenly scrape the other part of the heat-conducting mixture on the surface of the first heat-conducting layer, and form a second heat-conducting layer on the surface of the first heat-conducting layer after drying.
[0058] This can ensure that the thermal conductive layer is more evenly distributed on the substrate. The cross-coating method helps to eliminate the uneven coating that may occur when coating in a single direction. During the rotary coating process, the thermal conductive mixture can adhere more firmly to the nanofiber membrane under the action of centrifugal force. By coating in different directions, the bonding force between the thermal conductive layer and the nanofiber membrane can be further enhanced, thereby improving the durability of the nanocomposite membrane.
[0059] The technical solution of the present application will be described in more detail below, but it should be understood that the following examples are only for explaining and illustrating the technical solution, but do not limit the scope of the present application. Moreover, unless otherwise specified, the various raw materials, reaction equipment, detection equipment and methods used in the following examples are all known in the art.
[0060] Example 1
[0061] A method for preparing a nanocomposite film comprises steps S1 to S5.
[0062] Step S1: dissolving polymer powder in N,N-dimethylformamide to form a polymer solution.
[0063] Among them, the polymer is PVDF, and its molecular weight is 500,000.
[0064] Specifically, 8 g of PVDF powder was dissolved in 100 g of N,N-dimethylformamide, and the PVDF powder was completely dissolved after heating and stirring in a water bath at 85°C for 12 h, thereby obtaining a PVDF solution with a concentration of 8 wt %.
[0065] Step S2: adding nanoparticles into the polymer solution to form a nanocomposite solution.
[0066] Among them, the nanoparticles are SiO2, and their average particle size is 0.2um.
[0067] Specifically, 0.1 wt% SiO2 powder was added to the PVDF solution, and the mixture was heated and stirred in a water bath at 85°C for 2 h, and then ultrasonically dispersed for 30 min to obtain a uniform PVDF / SiO2 solution.
[0068] Step S3: preparing the nanocomposite solution into a nanofiber membrane through an electrospinning machine.
[0069] Specifically, the PVDF / SiO2 solution was placed in the syringe of an electrospinning machine, and a PVDF / SiO2 nanofiber membrane with a thickness of 50 um was prepared by using the electrospinning process and a "roll-to-roll" fiber collection method. The PVDF / SiO2 nanofiber membrane was then placed in a 100°C oven for 2 hours for drying to remove the solvent.
[0070] The flow rate of the PVDF / SiO2 solution was adjusted to 0.3 ml / h by the microinjection pump of the electrospinning machine; the voltage of the electrospinning was 10 KV; the temperature of the electrospinning was 30 ± 3; and the relative humidity of the electrospinning was 40% ± 5%.
[0071] Step S4: preparing a heat-conducting mixed liquid by using heat-conducting powder, silicone oil, hydrogen-containing silicone oil, inhibitor, catalyst and dispersant.
[0072] The thermal conductive powder is aluminum oxide with an average particle size of 0.8um, 5um, and 10um; the silicone oil is vinyl siloxane; the hydrogen-containing silicone oil is side hydrogen-containing silicone oil; the inhibitor is acetylene alcohol; the catalyst is a platinum catalyst; and the dispersant is DMC.
[0073] Specifically, 40 parts of each alumina with an average particle size of 0.8um, 5um, and 10um are taken and mixed evenly to obtain thermal conductive powder; 100 parts of thermal conductive powder are taken, and 1 part of vinyl siloxane, 0.05 parts of side hydrogenated silicone oil, 0.01 parts of acetylene alcohol, and 10 parts of DMC are added in sequence, and stirred evenly using a homogenizer, and then 0.01 parts of platinum catalyst are added, and then stirred evenly and vacuumed to degas to obtain a stable thermal conductive mixed liquid.
[0074] Step S5: using a coating machine to scrape the heat-conducting mixed liquid on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane to obtain a nanocomposite membrane.
[0075] The coating speed of the coater is 5 mm / s, and the blade gap of the coater is 1 mm.
[0076] Specifically, a part of the thermal conductive mixture is evenly scraped on the surface of the PVDF / SiO2 nanofiber membrane, and a 1mm first thermal conductive layer is formed on the surface of the PVDF / SiO2 nanofiber membrane after drying, and then it is placed in a 125°C oven for 1 hour for drying to remove the solvent and enhance the bonding force between molecules; then the PVDF / SiO2 nanofiber membrane with the first thermal conductive layer formed on the surface is rotated 90°, and another part of the thermal conductive mixture is evenly scraped on the surface of the first thermal conductive layer, and a 1mm second thermal conductive layer is formed on the surface of the first thermal conductive layer after drying, and then it is dried to obtain a nanocomposite membrane.
[0077] Example 2
[0078] A method for preparing a nanocomposite film comprises steps S1 to S5.
[0079] Step S1: dissolving polymer powder in N,N-dimethylformamide to form a polymer solution.
[0080] Among them, the polymer is PVDF, and its molecular weight is 700,000.
[0081] Specifically, 11 g of PVDF powder was dissolved in 100 g of N,N-dimethylformamide, and the PVDF powder was completely dissolved after heating in a water bath at 85°C with stirring for 12 h, thereby obtaining a PVDF solution with a concentration of 11 wt %.
[0082] Step S2: adding nanoparticles into the polymer solution to form a nanocomposite solution.
[0083] Among them, the nanoparticles are SiO2, and their average particle size is 6um.
[0084] Specifically, 0.3 wt % SiO2 powder was added to the PVDF solution, and the mixture was heated and stirred in a water bath at 85° C. for 2 h, and then ultrasonically dispersed for 30 min to obtain a uniform PVDF / SiO2 solution.
[0085] Step S3: preparing the nanocomposite solution into a nanofiber membrane through an electrospinning machine.
[0086] Specifically, the PVDF / SiO2 solution was placed in the syringe of an electrospinning machine, and a PVDF / SiO2 nanofiber membrane with a thickness of 50 um was prepared by using the electrospinning process and a "roll-to-roll" fiber collection method. The PVDF / SiO2 nanofiber membrane was then placed in a 100°C oven for 2 hours for drying to remove the solvent.
[0087] The flow rate of the PVDF / SiO2 solution was adjusted to 0.8 ml / h by the microinjection pump of the electrospinning machine; the voltage of the electrospinning was 20 KV; the temperature of the electrospinning was 30 ± 3; and the relative humidity of the electrospinning was 40% ± 5%.
[0088] Step S4: preparing a heat-conducting mixed liquid by using heat-conducting powder, silicone oil, hydrogen-containing silicone oil, inhibitor, catalyst and dispersant.
[0089] The thermal conductive powder is aluminum oxide with an average particle size of 0.8um, 5um, and 10um; the silicone oil is vinyl siloxane; the hydrogen-containing silicone oil is side hydrogen-containing silicone oil; the inhibitor is acetylene alcohol; the catalyst is a platinum catalyst; and the dispersant is DMC.
[0090] Specifically, 40 parts of each alumina with an average particle size of 0.8um, 5um, and 10um are taken and mixed evenly to obtain thermal conductive powder; 100 parts of thermal conductive powder are taken, and 5 parts of vinyl siloxane, 0.1 parts of side hydrogenated silicone oil, 0.05 parts of acetylene alcohol, and 25 parts of DMC are added in sequence, and stirred evenly using a homogenizer, and then 0.05 parts of platinum catalyst are added, and then stirred evenly and vacuumed to degas to obtain a stable thermal conductive mixed liquid.
[0091] Step S5: using a coating machine to scrape the heat-conducting mixed liquid on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane to obtain a nanocomposite membrane.
[0092] The coating speed of the coater is 5 mm / s, and the blade gap of the coater is 1 mm.
[0093] Specifically, a part of the thermal conductive mixture is evenly scraped on the surface of the PVDF / SiO2 nanofiber membrane, and a 1mm first thermal conductive layer is formed on the surface of the PVDF / SiO2 nanofiber membrane after drying, and then it is placed in a 125°C oven for 1 hour for drying to remove the solvent and enhance the bonding force between molecules; then the PVDF / SiO2 nanofiber membrane with the first thermal conductive layer formed on the surface is rotated 90°, and another part of the thermal conductive mixture is evenly scraped on the surface of the first thermal conductive layer, and a 1mm second thermal conductive layer is formed on the surface of the first thermal conductive layer after drying, and then it is dried to obtain a nanocomposite membrane.
[0094] Example 3
[0095] A method for preparing a nanocomposite film comprises steps S1 to S5.
[0096] Step S1: dissolving polymer powder in N,N-dimethylformamide to form a polymer solution.
[0097] Among them, the polymer is PVDF, and its molecular weight is 1 million.
[0098] Specifically, 14 g of PVDF powder was dissolved in 100 g of N,N-dimethylformamide, and the PVDF powder was completely dissolved after heating in a water bath at 85°C with stirring for 12 h, thereby obtaining a PVDF solution with a concentration of 14 wt %.
[0099] Step S2: adding nanoparticles into the polymer solution to form a nanocomposite solution.
[0100] Among them, the nanoparticles are SiO2, and their average particle size is 12um.
[0101] Specifically, 0.5 wt% SiO2 powder was added to the PVDF solution, and the mixture was heated and stirred in a water bath at 85°C for 2 h, and then ultrasonically dispersed for 30 min to obtain a uniform PVDF / SiO2 solution.
[0102] Step S3: preparing the nanocomposite solution into a nanofiber membrane through an electrospinning machine.
[0103] Specifically, the PVDF / SiO2 solution was placed in the syringe of an electrospinning machine, and a PVDF / SiO2 nanofiber membrane with a thickness of 50 um was prepared by using the electrospinning process and a "roll-to-roll" fiber collection method. The PVDF / SiO2 nanofiber membrane was then placed in a 100°C oven for 2 hours for drying to remove the solvent.
[0104] The flow rate of the PVDF / SiO2 solution was adjusted to 1.2 ml / h by the microinjection pump of the electrospinning machine; the voltage of the electrospinning was 30 KV; the temperature of the electrospinning was 30±3; and the relative humidity of the electrospinning was 40%±5%.
[0105] Step S4: preparing a heat-conducting mixed liquid by using heat-conducting powder, silicone oil, hydrogen-containing silicone oil, inhibitor, catalyst and dispersant.
[0106] The thermal conductive powder is aluminum oxide with an average particle size of 0.8um, 5um, and 10um; the silicone oil is vinyl siloxane; the hydrogen-containing silicone oil is side hydrogen-containing silicone oil; the inhibitor is acetylene alcohol; the catalyst is a platinum catalyst; and the dispersant is DMC.
[0107] Specifically, 40 parts of each alumina with an average particle size of 0.8um, 5um, and 10um are taken and mixed evenly to obtain thermal conductive powder; 100 parts of thermal conductive powder are taken, and 10 parts of vinyl siloxane, 0.2 parts of side hydrogenated silicone oil, 0.1 parts of acetylene alcohol, and 40 parts of DMC are added in sequence, and stirred evenly using a homogenizer, and then 0.1 parts of platinum catalyst are added, and then stirred evenly and vacuumed to degas to obtain a stable thermal conductive mixed liquid.
[0108] Step S5: using a coating machine to scrape the heat-conducting mixed liquid on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane to obtain a nanocomposite membrane.
[0109] The coating speed of the coater is 5 mm / s, and the blade gap of the coater is 1 mm.
[0110] Specifically, a part of the thermal conductive mixture is evenly scraped on the surface of the PVDF / SiO2 nanofiber membrane, and a 1mm first thermal conductive layer is formed on the surface of the PVDF / SiO2 nanofiber membrane after drying, and then it is placed in a 125°C oven for 1 hour for drying to remove the solvent and enhance the bonding force between molecules; then the PVDF / SiO2 nanofiber membrane with the first thermal conductive layer formed on the surface is rotated 90°, and another part of the thermal conductive mixture is evenly scraped on the surface of the first thermal conductive layer, and a 1mm second thermal conductive layer is formed on the surface of the first thermal conductive layer after drying, and then it is dried to obtain a nanocomposite membrane.
[0111] Example 4
[0112] The difference from Example 2 is that 12 g of PVDF powder is dissolved in 100 g of N,N-dimethylformamide, and the concentration of the PVDF solution is 12 wt %.
[0113] It can be seen from Examples 2 and 4 that as the concentration of the PVDF solution increases, the drop temperature of the radiation cooling increases and the thermal conductivity increases, which indicates that increasing the concentration of the PVDF solution can enhance the radiation cooling performance and thermal conductivity of the nanocomposite film.
[0114] Example 5
[0115] The difference from Example 2 is that 13 g of PVDF powder is dissolved in 100 g of N,N-dimethylformamide, and the concentration of the PVDF solution is 13 wt %.
[0116] It can be seen from Examples 2, 4 and 5 that as the concentration of PVDF solution continues to increase, the drop temperature of radiant cooling decreases and the thermal conductivity decreases, which means that when the concentration of PVDF solution is 12wt%, the radiant cooling performance and thermal conductivity of the nanocomposite membrane are optimal.
[0117] Example 6
[0118] The difference from Example 2 is that the mass fraction of SiO2 powder is 0.2wt%.
[0119] It can be seen from Examples 2 and 6 that as the mass fraction of SiO2 increases, the drop temperature of the radiation cooling increases and the thermal conductivity increases, which indicates that increasing the mass fraction of SiO2 can enhance the radiation cooling performance and thermal conductivity of the nanocomposite film.
[0120] Example 7
[0121] The difference from Example 2 is that the mass fraction of SiO2 powder is 0.4wt%.
[0122] It can be seen from Examples 2, 6 and 7 that as the mass fraction of SiO2 continues to increase, the drop temperature of the radiation cooling decreases and the thermal conductivity decreases, which indicates that when the mass fraction of SiO2 is 0.3wt%, the radiation cooling performance of the nanocomposite film is better.
[0123] Example 8
[0124] The difference from Example 2 is that 30 parts of aluminum oxide with an average particle size of 0.8 um, 30 parts of aluminum oxide with an average particle size of 5 um, and 60 parts of aluminum oxide with an average particle size of 10 um are mixed evenly to obtain a thermally conductive powder.
[0125] Example 9
[0126] The difference from Example 2 is that 20 parts of aluminum oxide with an average particle size of 0.8 um, 30 parts of aluminum oxide with an average particle size of 5 um, and 60 parts of aluminum oxide with an average particle size of 10 um are mixed evenly to obtain a thermally conductive powder.
[0127] Example 10
[0128] 20 parts of aluminum oxide with an average particle size of 0.8 um, 40 parts of aluminum oxide with an average particle size of 5 um, and 60 parts of aluminum oxide with an average particle size of 10 um are mixed evenly to obtain a thermally conductive powder.
[0129] It can be seen from Examples 2 and 8-10 that as the weight ratio between alumina particles of different sizes increases, the radiative cooling drop temperature increases significantly and the thermal conductivity increases significantly, which indicates that increasing the weight ratio between alumina particles of different sizes can significantly enhance the radiative cooling and thermal conductivity of the nanocomposite film, among which the radiative cooling and thermal conductivity effects are best at a weight ratio of 1:2:3.
[0130] Embodiment 11
[0131] The difference from Example 2 is that the amount of hydrogenated silicone oil is 0.14 parts.
[0132] It can be seen from Examples 2 and 11 that with the increase of hydrogen-containing silicone oil, the radiant cooling drop temperature will decrease and the thermal conductivity will decrease, which means that the increase of hydrogen-containing silicone oil content will reduce the radiant cooling performance and thermal conductivity of the nanocomposite film.
[0133] Example 12
[0134] The difference from Example 2 is that the amount of hydrogenated silicone oil is 0.16 parts.
[0135] It can be seen from Examples 2, 11 and 12 that when the content of hydrogen-containing silicone oil exceeds 0.14 g, the falling temperature of radiant cooling will continue to decrease, the thermal conductivity will continue to decrease, and the nano-composite film will have obvious creases when folded in half. This is because when the content of hydrogen-containing silicone oil is large, the hardness of the coating increases significantly, which makes it easy to produce creases when folded in half.
[0136] Embodiment 13
[0137] The difference from Example 2 is that the thermally conductive powder is AlN.
[0138] It can be seen from Examples 2 and 13 that when the thermally conductive powder is AlN, the drop temperature of the radiation cooling does not change much, and the thermal conductivity increases. This indicates that when the thermally conductive powder is AlN, the thermal conductivity of the nanocomposite film will be better.
[0139] Comparative Example
[0140] The preparation of the nanocomposite film is as follows:
[0141] 8g of PVDF powder was dissolved in 100g of N,N-dimethylformamide, and the PVDF powder was completely dissolved after heating and stirring in a water bath at 85℃ for 12h to obtain a PVDF solution with a concentration of 8wt%. The PVDF membrane was prepared by an electrospinning process and a "roll-to-roll" fiber collection method, and then the PVDF membrane was placed in a 100℃ oven for 2h for drying to remove the solvent. The flow rate of the PVDF solution was adjusted to 0.3ml / h by the microinjection pump of the electrospinning machine; the voltage was 10KV; the temperature was 30℃±3℃; and the relative humidity was 40%±5%.
[0142] 0.01 g of SIO2 powder with an average particle size of 0.2 um was dissolved in 100 g of anhydrous ethanol to prepare a SIO2 / anhydrous ethanol dispersion with a mass fraction of 0.01 wt%. The dispersion was treated with an ultrasonic instrument and a high-speed disperser for 30 minutes. The obtained PVDF membrane was placed in the dispersion and continued to be treated with an ultrasonic instrument for 20 minutes to obtain a PVDF / SiO2 nanofiber membrane.
[0143] A thermally conductive mixed liquid is prepared by using thermally conductive powder, silicone oil, hydrogen-containing silicone oil, an inhibitor, a catalyst and a dispersant.
[0144] The thermal conductive powder is aluminum oxide with an average particle size of 0.8um, 5um, and 10um; the silicone oil is vinyl siloxane; the hydrogen-containing silicone oil is side hydrogen-containing silicone oil; the inhibitor is acetylene alcohol; the catalyst is a platinum catalyst; and the dispersant is DMC.
[0145] Specifically, 40 parts of each alumina with an average particle size of 0.8um, 5um, and 10um are taken and mixed evenly to obtain thermal conductive powder; 100 parts of thermal conductive powder are taken, and 1 part of vinyl siloxane, 0.05 parts of side hydrogenated silicone oil, 0.01 parts of acetylene alcohol, and 10 parts of DMC are added in sequence, and stirred evenly using a homogenizer, and then 0.01 parts of platinum catalyst are added, and then stirred evenly and vacuumed to degas to obtain a stable thermal conductive mixed liquid.
[0146] The heat-conducting mixed liquid is scraped on the surface of the PVDF / SiO2 nanofiber membrane by using a coating machine to form a heat-conducting layer on the PVDF / SiO2 nanofiber membrane to obtain a nanocomposite membrane.
[0147] The coating speed of the coater is 5 mm / s, and the blade gap of the coater is 1 mm.
[0148] Specifically, a part of the thermal conductive mixture is evenly scraped on the surface of the PVDF / SiO2 nanofiber membrane, and a 1mm first thermal conductive layer is formed on the surface of the PVDF / SiO2 nanofiber membrane after drying, and then it is placed in a 125°C oven for 1 hour for drying to remove the solvent and enhance the bonding force between molecules; then the PVDF / SiO2 nanofiber membrane with the first thermal conductive layer formed on the surface is rotated 90°, and another part of the thermal conductive mixture is evenly scraped on the surface of the first thermal conductive layer, and a 1mm second thermal conductive layer is formed on the surface of the first thermal conductive layer after drying, and then it is dried to obtain a nanocomposite membrane.
[0149] It can be seen from the comparative examples and Example 1 that SiO2 is first dissolved in a PVDF solution to prepare a PVDF / SiO2 solution, and then the PVDF / SiO2 solution is used to prepare a PVDF / SiO2 nanofiber membrane, and finally a nanocomposite membrane is prepared by the PVDF / SiO2 nanofiber membrane. The radiation refrigeration performance and thermal conductivity of the nanocomposite membrane are significantly better than those of first preparing a PVDF membrane by using a PVDF solution, then preparing a PVDF / SiO2 nanofiber membrane by using a PVDF membrane and a SIO2 / anhydrous ethanol dispersion, and finally preparing a nanocomposite membrane by using a PVDF / SiO2 nanofiber membrane.
[0150] In order to verify the performance of the product of the present application, the following tests were performed on the nanocomposite films of the above embodiments and comparative examples. The test results are shown in Table 1.
[0151] (1) Thermal conductivity test
[0152] The thermal conductivity of the nanocomposite films of the above examples and comparative examples was tested using a thermal conductivity meter according to the method in ASTM D 5470-2001.
[0153] (2) Testing method for radiant cooling performance test: A polystyrene foam box is completely covered with aluminum foil, the nanocomposite film is placed in the foam box, and the thermocouple of the temperature measuring instrument is placed under the nanocomposite film, so as to measure the cooling temperature (drop temperature) of the nanocomposite film by the temperature measuring instrument.
[0154] (3) Appearance: When the nanocomposite film is folded in half, it takes an arc shape. When it is released, it returns to its original shape. The nanocomposite film does not break, indicating that the nanocomposite film has good softness.
[0155] Table 1: Test results of Examples 1-13 and Comparative Examples
[0156] Example Drop temperature(℃) Thermal conductivity (W / m*K) Apparent state Example 1 1.03 0.54 Soft without creases Example 2 1.79 0.75 Soft without creases Example 3 3.53 0.96 Soft without creases Example 4 4.51 1.51 Soft without creases Example 5 2.14 1.07 Soft with creases Example 6 1.65 0.6 Soft without creases Example 7 1.68 0.68 Soft without creases Example 8 2.12 0.96 Soft without creases Example 9 2.24 1.05 Soft without creases Example 10 2.32 1.38 Soft without creases Embodiment 11 1.67 0.65 Soft without creases Example 12 1.32 0.6 Soft with creases Embodiment 13 1.8 1 Soft without creases Comparative Example 0.75 0.32 Soft without creases
[0157] It can be seen from the above test results that the nanocomposite film of the present application has at least the following beneficial effects:
[0158] The nanocomposite film of the present application has a temperature drop of more than 1°C for radiation cooling and a thermal conductivity of more than 0.5W / m*K. It not only has good radiation cooling performance and thermal conductivity, but also has a thickness of less than 3mm, thus realizing ultra-thinness of the nanocomposite film.
[0159] Embodiment 4 is the best embodiment. The maximum temperature drop of radiant cooling can reach 4.51°C, the thermal conductivity is 1.51W / m*K, and it has good softness.
[0160] It can be seen from Examples 2 and 4 that as the concentration of the PVDF solution increases, the drop temperature of the radiation cooling increases and the thermal conductivity increases, which indicates that increasing the concentration of the PVDF solution can enhance the radiation cooling performance and thermal conductivity of the nanocomposite film.
[0161] It can be seen from Examples 2, 4 and 5 that as the concentration of PVDF solution continues to increase, the drop temperature of radiant cooling decreases and the thermal conductivity decreases, which means that when the concentration of PVDF solution is 12wt%, the radiant cooling performance and thermal conductivity of the nanocomposite membrane are optimal.
[0162] It can be seen from Examples 2 and 6 that as the mass fraction of SiO2 increases, the drop temperature of the radiation cooling increases and the thermal conductivity increases, which indicates that increasing the mass fraction of SiO2 can enhance the radiation cooling performance and thermal conductivity of the nanocomposite film.
[0163] It can be seen from Examples 2, 6 and 7 that as the mass fraction of SiO2 continues to increase, the drop temperature of the radiation cooling decreases and the thermal conductivity decreases, which indicates that when the mass fraction of SiO2 is 0.3wt%, the radiation cooling performance of the nanocomposite film is better.
[0164] It can be seen from Examples 2 and 8-10 that as the weight ratio of alumina with different particle sizes increases, the radiative cooling drop temperature increases significantly and the thermal conductivity increases significantly, which indicates that increasing the weight ratio of alumina with different particle sizes can significantly enhance the radiative cooling performance and thermal conductivity of the nanocomposite film.
[0165] It can be seen from Examples 2 and 11 that with the increase of hydrogen-containing silicone oil, the radiant cooling drop temperature will decrease and the thermal conductivity will decrease, which means that the increase of hydrogen-containing silicone oil content will reduce the radiant cooling performance and thermal conductivity of the nanocomposite film.
[0166] It can be seen from Examples 2, 11 and 12 that when the content of hydrogen-containing silicone oil exceeds 0.14 g, the falling temperature of radiant cooling will continue to decrease, the thermal conductivity will continue to decrease, and the nano-composite film will have obvious creases when folded in half. This is because when the content of hydrogen-containing silicone oil is large, the hardness of the coating increases significantly, which makes it easy to produce creases when folded in half.
[0167] It can be seen from Examples 2 and 13 that when the thermally conductive powder is AlN, the drop temperature of the radiation cooling does not change much, and the thermal conductivity increases. This indicates that when the thermally conductive powder is AlN, the thermal conductivity of the nanocomposite film will be better.
[0168] It can be seen from the comparative examples and Example 1 that SiO2 is first dissolved in a PVDF solution to prepare a PVDF / SiO2 solution, and then a PVDF / SiO2 nanofiber membrane is prepared using the PVDF / SiO2 solution, and finally a nanocomposite membrane is prepared using the PVDF / SiO2 nanofiber membrane. The radiation refrigeration performance and thermal conductivity of the nanocomposite membrane are significantly better than those of first preparing a PVDF membrane using a PVDF solution, then preparing a PVDF / SiO2 nanofiber membrane using a PVDF membrane and a SIO2 / anhydrous ethanol dispersion, and finally preparing a nanocomposite membrane using a PVDF / SiO2 nanofiber membrane.
[0169] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the application without departing from the principles and purpose of the present application. All of these changes should fall within the scope of protection of the claims of the present application.
Claims
1. A method for preparing a nanocomposite film, characterized in that: include: dissolving polymer powder in N,N-dimethylformamide to form a polymer solution; Adding nanoparticles to the polymer solution to form a nanocomposite solution, wherein the nanoparticles have selective emission characteristics; preparing a nanofiber membrane using the nanocomposite solution; A thermally conductive mixed liquid is prepared by using thermally conductive powder, silicone oil, hydrogen-containing silicone oil, inhibitor, catalyst and dispersant; The heat-conducting mixed liquid is scraped on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane to obtain a nanocomposite membrane.
2. The preparation method according to claim 1, characterized in that: The heat-conducting layer comprises a first heat-conducting layer and a second heat-conducting layer which are stacked in sequence; and coating the heat-conducting mixed liquid on the surface of the nanofiber membrane to form a heat-conducting layer on the nanofiber membrane comprises: Evenly scraping a portion of the heat-conducting mixed liquid on the surface of the nanofiber membrane, and forming a first heat-conducting layer on the surface of the nanofiber membrane after drying; The nanofiber membrane with the first heat-conducting layer formed on the surface is rotated 90 degrees, another part of the heat-conducting mixed liquid is evenly scraped on the surface of the first heat-conducting layer, and a second heat-conducting layer is formed on the surface of the first heat-conducting layer after drying.
3. The preparation method according to any one of claims 1 or 2, characterized in that: In the nano composite solution, the mass fraction of the polymer solution is 8wt% to 14wt%; the mass fraction of the nano particles is 0.1wt% to 0.5wt%.
4. The preparation method according to claim 3, characterized in that: In parts by weight, the thermally conductive powder comprises 100 parts; the silicone oil comprises 1 to 10 parts; the hydrogen-containing silicone oil comprises 0.05 to 0.2 parts; the inhibitor comprises 0.01 to 0.1 parts; the catalyst comprises 0.01 to 0.1 parts; and the dispersant comprises 10 to 40 parts.
5. The preparation method according to claim 1, characterized in that: The nanocomposite solution is used to prepare a nanofiber membrane by an electrospinning machine, comprising: The nanocomposite solution is placed in a syringe of an electrospinning machine to prepare a nanofiber membrane using an electrospinning process; The flow rate of the nanocomposite solution is 0.3-1.2 ml / h; the voltage of the electrostatic spinning is 10-30 KV; the temperature of the electrostatic spinning is 30±3; and the relative humidity of the electrostatic spinning is 40%±5%.
6. The preparation method according to claim 1, characterized in that: The polymer includes one or more of PVDF, PVC, PI, PU, and TPX; and / or the molecular weight of the polymer is 500,000-1,000,000.
7. The preparation method according to claim 1, characterized in that: The nanoparticles include one or more of SiO2, ZnO, Al2O3, TiO2, and ZnS; and / or the average particle size of the nanoparticles is 0.2 to 12 um.
8. The preparation method according to claim 1, characterized in that: The thermally conductive powder includes one or more of Al2O3, AlN, BN, Si3N4, Al(OH)3, Ag, and diamond; and / or the average particle size of the thermally conductive powder is 0.4 to 20 um.
9. The preparation method according to claim 1, characterized in that: The silicone oil includes one or more of vinyl silicone, methylphenyl silicone, polydimethyl silicone, and hydroxy silicone.
10. The preparation method according to claim 1, characterized in that: The hydrogen-containing silicone oil includes one or more of terminal hydrogen-containing silicone oil and side hydrogen-containing silicone oil.
11. The preparation method according to claim 1, characterized in that: The inhibitor includes one or more of acetylene alcohols, alkynyl siloxanes, and nitrates.
12. The preparation method according to claim 1, characterized in that: The catalyst includes one or more of an organic tin catalyst, an organic chromium catalyst, a platinum catalyst, and an organic titanium catalyst.
13. The preparation method according to claim 1, characterized in that: The selected dispersant includes one or more of ethylene glycol, xylene, butyl ester, and dimethyl carbonate.